2023
DOI: 10.3171/2023.2.spine2392
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of balloon kyphoplasty for osteoporotic vertebral fractures with diffuse idiopathic skeletal hyperostosis

Abstract: OBJECTIVE The authors aimed to determine the poor prognostic factors of balloon kyphoplasty for the treatment of fractures of the most distal or distal-adjacent vertebrae in ankylosing spines with diffuse idiopathic skeletal hyperostosis (DISH). METHODS Eighty-nine patients with fractures of the most distal or distal-adjacent vertebrae of ankylosing spines with DISH were included and divided into two groups: those with (n = 51) and without (n = 38) bone healing 6 months postoperatively. Clinical evaluation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The VBS procedure, introduced as a new option for vertebral cement augmentation, has an advantage over BKP in that the stent maintains the restored vertebral body height after intravertebral reduction [11]. Some reports have demonstrated the usefulness of cement augmentation for vertebral fractures in ankylosing spines, including DISH [12][13][14]. Tsuchikawa et al reported improved VAS and Oswestry Disability Index (ODI) scores in patients undergoing BKP surgery for fractures of the distal or distally adjacent vertebrae of DISH [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VBS procedure, introduced as a new option for vertebral cement augmentation, has an advantage over BKP in that the stent maintains the restored vertebral body height after intravertebral reduction [11]. Some reports have demonstrated the usefulness of cement augmentation for vertebral fractures in ankylosing spines, including DISH [12][13][14]. Tsuchikawa et al reported improved VAS and Oswestry Disability Index (ODI) scores in patients undergoing BKP surgery for fractures of the distal or distally adjacent vertebrae of DISH [14].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have demonstrated the usefulness of cement augmentation for vertebral fractures in ankylosing spines, including DISH [12][13][14]. Tsuchikawa et al reported improved VAS and Oswestry Disability Index (ODI) scores in patients undergoing BKP surgery for fractures of the distal or distally adjacent vertebrae of DISH [14]. Even without posterior fixation, cement augmentation procedures contribute effectively to stabilizing vertebral fractures in some DISH patients.…”
Section: Discussionmentioning
confidence: 99%
“…62 These results were also demonstrated when kyphoplasty was used instead of vertebroplasty. 63,64 Additionally, bracing with anti-osteoporotic treatment is believed to contribute to improved quality of life for the patient. 63 However, Tsuchikawa et al recommend avoiding this technique in patients with a difference ≥ 10° in the wedge angle of the fractured vertebrae between the supine and sitting positions as it was associated with delayed healing.…”
Section: Vertebroplasty and Kyphoplastymentioning
confidence: 99%